PENGETAHUAN DAN SIKAP TERHADAP IMUNISASI TETANUS TOXOID DENGAN KELENGKAPAN IMUNISASI IBU HAMIL DI KABUPATEN INDRAGIRI HULU RIAU - , Ruspa Nora ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: About 9.8% of 184 thousand births died of tetanus. the high incidence of tetanus-related maternal behaviors that are not immunized against tetanus toxoid during pregnancy. Research shows the effectiveness of TT vaccination reduced mortality due to neonatal tetanus. TT2 immunization coverage in Indragiri Hulu by 35.5% and still lower than the national target of 85%.knowledge, attitudes, frequency of antenatal care, education and information about the TT can affect the mother's decision to obtain a complete TT immunization. Objective: Assess knowledge and attitudes in relation to the completeness of maternal TT immunization among pregnant women in Indragiri Hulu Riau in 2010. Method: Type of observational research with cross sectional design with quantitative and qualitative approaches. research subjects is the mother who gave birth in 2011 at the Health Center Sipayung, last week surprised and comely water. Number of samples this study as much as 293. Sampling using a multistage sampling designs with a purposive and simple random sampling. Quantitative data analysis through three stages, namely: univariabel analysis, and multivariable bivariabel plus qualitative analysis. Result: The result of logistic regression analysis showed a significant association between knowledge and attitude toward immunization completeness TT (RP= 2,8, 95% CI: 1,68-4,73) by controlling the variable antenatal care (RP=4,00, 95% CI: 2,35-6,83), the variable education (RP= 2,06, 95% CI: 1,22-3,48) can predict TT immunization completeness of 15,01%. The result of indepth interview indicate a lack of information about the benefits of midwifery and TT immunization for pregnant women immunized fear was a factors contributing to complete TT immunization of pregnant women. conclusion: A mother with a good knowledge and positive attitudes tend to be higher to get a complete TT immunization. Antenatal care and maternal education has a significant relationship with the practical and theoretical completeness TT immunization of pregnant women